Enterobacter cloacae Postsurgical Endophthalmitis: Report of a Positive Outcome - Scott Butikofer; Jason M. Dettori; G. Atma Vemulakonda; Mark Slabaugh (Case Reports in Ophthalmology, 2013)
We report a positive outcome of postcataract endophthalmitis caused by Enterobacter cloacae, which has previously resulted in poor outcomes in endophthalmitis. A 67-year-old man underwent uncomplicated cataract surgery. On the morning of postoperative day (POD) #1, he had significant anterior chamber inflammation without pain, hypopyon, or vitritis but then rapidly developed hypopyon and worsening visual acuity. He underwent a tap and inject with vancomycin and ceftazidime and was prescribed topical steroids and antibiotics as well as oral levofloxacin. On POD #3, cultures of the vitreous and aqueous returned positive for E. cloacae. By POD #6, his hypopyon had resolved with improved vitritis, decreased inflammation, and visual acuity of 20/200. Two weeks after surgery, his best-corrected visual acuity was 20/60. Contrary to prior reports, we demonstrate that it is possible to achieve a good outcome in cases of E. cloacae endophthalmitis treated early with appropriate antibiotics and anti-inflammatory agents.